PROGNOSTICATION OF STRAIN-STRENGTH CHARACTERISTICS OF STRUCTURAL PARTICLEBOARDS DURING CONTINUOUS STATIC BENDING LOAD (Innovation in Woodworking Industry and Engineering design, 2026)
Subject of the investigation is the prognostication of the resistance of structural three- and multilayer particleboards (SPB) to continuous static bending load under the conditions of rela-tively dry environment. The theoretical prerequisites of the development are the rheological model of SPB and the schematic diagram of their deformation during continuous load, the algo-rithm and the nomogram to determine the stiffness of SPB on the basis of their simulation model of a “double T-beam” and the regression dependences of the moduli of elasticity of SPB with various thicknesses on their volumetric density.An algorithm and a nomogram to determine the continuous load factor of SPB to prognosticate their resistance as structural elements in furniture and building structures have been pro-posed. The creep coefficient of composite particleboards under operating conditions has been determined.